Effect of splinting material type and location on resistance against deflection force of splinted periodontally compromised teeth with hypermobility. (June 2023) - Wada, Junichiro; Wada, Kanae; Uctasli, Sadullah; Wakabayashi, Noriyuki; Iwamoto, Tsutomu; Vallittu, Pekka K.; Lassila, Lippo
Abstract: This study aimed to evaluate the effect of splinting material type and material location on the force resistance of splinted periodontally compromised teeth with hypermobility. Extracted teeth including the target tooth (maxillary second premolar) and its adjacent teeth were placed into the alveolar sockets of a dental arch model via artificial periodontal ligaments made of elastic impression material. Three different experimental models with varied target tooth mobility including Periotest® values (PTVs) of 20, 30, and 40 were fabricated (named models #20, #30, and #40, respectively). For each experimental model, the force resistance of tooth splinting was tested using the following four materials: everStick PERIO (glass fiber reinforcement: GFR), FORESTAFLEX (braided stainless steel: BSS), Ortho-FlexTech (stainless steel chain: SSC), and Super-Bond (MMA-based resin cement: MRC). The evaluated measures were the PTV after tooth splinting and the required load to cause tooth displacements of 0.05 mm and 0.10 mm in the vertical and lateral directions, respectively. The splinting material type and material location as well as the original PTV of target the tooth significantly affected all the evaluated measures ( p  < 0.001). MRC revealed the significantly highest force resistance of tooth splinting regardless of material location in each experimental model and was followed by GFR. The PTVs of splinted teeth were comparable to those of adjacent anchor teeth in models #20 and #30 when using GFR, while that was comparable in model #40 when using MRC. Meanwhile, the load causing certain tooth displacement showed a similar tendency to previous-reported data with healthy teeth in model #20 when using GFR, while that showed a similar tendency in models #30 and #40 when using MRC. Overall results concluded that splinting material type and location play a role in the resistance against the deflection force of splinted periodontally compromised hypermobile tooth. It was noted that MRC provided the highest resistance against the deflection force of splinted teeth regardless of material location whereas GFR maintained the physiologically considered tooth mobility. Graphical abstract: Image 1 Highlights: MMA-based resin provides higher resistance to periodontally compromised tooth. Physiologic tooth mobility is maintained when splinted by glass fiber reinforcement. MMA-based resin is recommended to splint tooth with severe hypermobility. Glass fiber reinforcement is recommended to splint tooth with slight hypermobility.